Indicadores de gestión de la innovación que determine ventajas competitivas en el hotel Los Almendros de la ciudad de Manta - Álvarez Mendoza, Bárbara Elizabeth (2022)
In order to determine the competitive advantages of the Los Almendros de Manta hotel, innovation management indicators were established. The investigation was developed in three phases beginning with the characterization of the lodging where it was determined through a file supported by the bibliographic and documentary review that the company presents a series of problems that limit its efficient operation, which according to the interviews staff is due to poor management and measurement of innovation to position themselves favorably in the market. In the second stage, after the bibliographic review, 16 indicators associated with the functions of innovation were selected, which were validated by the criteria of 7 experts with the Delphi method, where, in addition, the 7S Mckinsey matrix detected that the general performance of the hotel in relation to the innovation strategy is low and that the main competitive advantages are the availability and quality of services, management and its management, innovations, technology, among others. In the last phase, the improvement plan was structured in a matrix that contemplates 16 actions linked to the innovative processes (product, process, organization and marketing) with their respective managers and indicators, the latter were established based on the inventory functions, monitor, enrich, evaluate, optimize and protect that together seek to contribute to the promotion of the competitive advantages of Hotel Los Almendros.